2021
DOI: 10.4274/jcrpe.galenos.2020.2020.0004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Difficulties in Hypomagnesemia Secondary to the Transient Receptor Potential Melastatin 6 Gene: A Case Report with Novel Mutation

Abstract: What's known on this topic? Hypomagnesemia is one of the causes of hypocalcemia. Enteral replacement is the key in the treatment but the treatment should be individualized for each patient. Normalization of hypomagnesemia is not always easy and should not be the aim of the treatment. What this study adds? The genetic analysis revealed a novel frame shift variant in the transient receptor potential melastatin 6 genes. The magnesium levels varied during the treatment with different preparations of medication. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, in our case, a history of febrile convulsions in the patient and his maternal family members could disrupt the initial diagnosis, which may be explained by the fact that fever intensifies the convulsions caused by hypomagnesemia. The previous literature also showed 3 patient had a history of febrile convulsions, 2 didn't complete the serum examination, 1 occurred after diagnosed (12,30,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our case, a history of febrile convulsions in the patient and his maternal family members could disrupt the initial diagnosis, which may be explained by the fact that fever intensifies the convulsions caused by hypomagnesemia. The previous literature also showed 3 patient had a history of febrile convulsions, 2 didn't complete the serum examination, 1 occurred after diagnosed (12,30,34).…”
Section: Discussionmentioning
confidence: 99%
“…HypoMg has been long associated with increased seizure activities and epilepsy 1 4 , 37 . We have found that a low-Mg diet induces seizures and death, with female mice being more susceptible than males 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in both TRPM6 and TRPM7 have been associated with HypoMg and seizures 2 , 4 , 5 . Moreover, Mg supplementation can prevent these seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation